2009
DOI: 10.1016/j.eururo.2009.03.073
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 Trial of High-Dose Exogenous Testosterone in Patients with Castration-Resistant Metastatic Prostate Cancer

Abstract: Background-Growth of selected castration-resistant prostate cancer (CRPC) cell lines and animal models can be repressed by reexposure to androgens. Low doses of androgens, however, can stimulate tumor growth.Objective-We performed a phase 1 clinical trial to determine the safety of high-dose exogenous testosterone in patients with castration-resistant metastatic prostate cancer (CRMPC).Design, setting, and participants-Patients with progressive CRMPC who had been castrate for at least 1 yr received three times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 16 publications
1
65
0
Order By: Relevance
“…Fowler and Whimore, (1981) observed that out of 52 metastatic prostate cancer patients who received ART, 45 exhibited increased cancer progression that could be reversed by androgen withdrawal, whereas 7 experienced symptomatic benefits. Other investigators have observed that in patients with castration-resistant metastatic prostate cancer, ART resulted in either little adverse effect on cancer progression or displayed some biochemical improvement or progression (Mathew, 2008;Morris et al, 2009;Szmulewitz et al, 2009). These clinical studies suggested that prostate cancer patients have differential responses to androgen/AR signals and ART might be able to improve the quality of life in selective prostate cancer patients with little impact on further progression of their prostate cancers.…”
Section: Art In Prostate Cancer Patientsmentioning
confidence: 95%
“…Fowler and Whimore, (1981) observed that out of 52 metastatic prostate cancer patients who received ART, 45 exhibited increased cancer progression that could be reversed by androgen withdrawal, whereas 7 experienced symptomatic benefits. Other investigators have observed that in patients with castration-resistant metastatic prostate cancer, ART resulted in either little adverse effect on cancer progression or displayed some biochemical improvement or progression (Mathew, 2008;Morris et al, 2009;Szmulewitz et al, 2009). These clinical studies suggested that prostate cancer patients have differential responses to androgen/AR signals and ART might be able to improve the quality of life in selective prostate cancer patients with little impact on further progression of their prostate cancers.…”
Section: Art In Prostate Cancer Patientsmentioning
confidence: 95%
“…No adverse effect was reported. The serum testosterone ranged from 330-870 ng/dl (Morris et al 2009). This study suggested that patients with advanced prostate cancer can be safely treated with exogenous testosterone.…”
Section: Androgen Treatment Of Advanced Prostate Cancer In Clinicalmentioning
confidence: 92%
“…Bruchovsky et al showed that IAS therapy cause repeated differentiation of tumor with recovery of apoptotic potential, inhibition of tumor growth by rapid restoration of serum testosterone, and restraint of tumor growth by subnormal levels of serum testosterone (Bruchovsky et al 2000). They concluded that IAS is a viable treatment option for men with prostate cancer which affords an improved quality of life as well as reduced toxicity and costs (Bruchovsky et al 2000, Morris et al 2009, Pether et al 2003. A few studies have shown that androgen is safe and potentially effective for treatment of advanced prostate cancer.…”
Section: Androgen Treatment Of Advanced Prostate Cancer In Clinicalmentioning
confidence: 99%
“…The permanent methods of androgen ablation such as surgical castration can be replaced by reversible methods of castration such as medical castration with LHRH analogues. Interestingly, some investigators have even observed that using androgen replacement therapy (ART) in metastatic CRPC displayed biochemical improvement in patients [24]. Newer therapies targeting the prostate cancer stromal cells should be evaluated.…”
Section: Resultsmentioning
confidence: 99%